Global aid allocation: Are Nordic donors different? - Gates, S; Hoeffler, A (2004)
The Nordic development assistance programs have earned a reputation for commitment to human rights and democracy. Is the reputation deserved? We address this question by comparing how much aid donors give and to which recipient countries. Using a global panel data set, spanning the period 1980-99 and 91 recipient countries, we find that individual bilateral donors vary considerably from one another. Nordic aid distribution differs significantly from other bilateral aid donor patterns: Norway, Denmark, Sweden and Finland provide more aid to democracies but do not penalise poor trade policies. Unlike other bilateral donors the four Nordics do not provide more aid to political allies. We also find some evidence that recipients with a good human rights record receive more aid from Nordic donors.